2022
DOI: 10.3390/su14137615
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Agri-Food SMEs in Italy in the Post-COVID-19 Context: From Horizon 2020 to Horizon Europe

Abstract: In recent decades, European policy has targeted specific measures towards SMEs. The recently concluded Horizon 2020 Programme, under the Europe 2020 Strategy, has provided economic support to stimulate competitiveness and boost the economy of member states by focusing on innovation. The SME Instrument, through a structure of multiple calls, constituted the vehicle for SMEs to access the funds made available by the European Union with disruptive innovation proposals. The initial structure of the SME Instrument,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Even small neighborhood shops equipped themselves with their own platforms or used social media, such as Facebook and WhatsApp, to sell their products (Scuderi et al, 2022). In this regard, the pandemic has caused drastic changes in both sales and purchasing patterns (Zarbà et al, 2022) but, however, it is not yet sufficiently clear whether the post-COVID-19 situation will still be the same and whether online platforms will continue to be preferred by consumers. A recent market study showed that 61% of respondents said they would continue to shop online even after the pandemic (McKinsey and Company, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Even small neighborhood shops equipped themselves with their own platforms or used social media, such as Facebook and WhatsApp, to sell their products (Scuderi et al, 2022). In this regard, the pandemic has caused drastic changes in both sales and purchasing patterns (Zarbà et al, 2022) but, however, it is not yet sufficiently clear whether the post-COVID-19 situation will still be the same and whether online platforms will continue to be preferred by consumers. A recent market study showed that 61% of respondents said they would continue to shop online even after the pandemic (McKinsey and Company, 2020b).…”
Section: Introductionmentioning
confidence: 99%